Clinical and molecular characterization and response to acitretin in three families with Sjögren‐Larsson syndrome. (27th April 2018) - Vural, Seçil; Vural, Atay; Akçimen, Fulya; Bağci, Işın S.; Tunca, Ceren; Gündoğdu Eken, Asli; Ruzicka, Thomas; Başak, A. Nazli
Abstract: Introduction: Sjögren‐Larsson syndrome (SLS) is a rare congenital disorder characterized by the triad of ichthyosis, spasticity, and mental retardation. Patients are usually referred to dermatology clinics during infancy. As paraplegia becomes the most debilitating symptom of the disease within a few years, ichthyosis, although a major burden for the patient, takes a back seat. Optimum treatment of ichthyosis in these children and the effect of treatment on different aspects such as severity of the ichthyosis, pruritus, or quality of life of the patients' and their caregivers is not well established. Materials and Methods: Genetic background of eight patients from three families diagnosed clinically with SLS was determined with whole‐exome and Sanger sequencing. Clinical phenotypes, laboratory findings, magnetic resonance imaging (MRI), and treatment of the ichthyosis with acitretin were assessed. Results: All patients had the classical triad of Sjögren‐Larsson syndrome. Genetic analysis revealed that one patient had a novel c.799‐1 (+/+) homozygous splicing mutation in the ALDH3A2 gene. Other patients had the c.683G>A p.R228H (NM_000382.2) mutation in the same gene. Other manifestations included skeletal anomalies, enamel hypoplasia, bilateral T2‐hyperintensities in white matter, and moderate–severe pruritus. Acitretin treatment in a maintenance dose of 0.25 mg/kg/day decreased the severity of ichthyosis in all children. It increased quality of life significantly in all of the children and their caregivers. Conclusion: We conclude that ichthyosis can be treated effectively with low‐dose acitretin in children with Sjögren‐Larsson syndrome, and this treatment is associated with a significant improvement in the quality of life.